28.5k views
4 votes
Use the substitution method to solve the system of equations. 5x + 2y = 1 y = –x + 2

2 Answers

1 vote
Plug in y to equation
Distribute
Subtract 4 on each side
Add like terms
Divide

Plug in x to y equation
Distribute add like terms
Use the substitution method to solve the system of equations. 5x + 2y = 1 y = –x + 2-example-1
User Morten Kristensen
by
6.0k points
1 vote

Answer:

X = -1

Explanation:

Rewrite equations:

y = -x + 2; 5x + 2y = 1

Step: Solve y = -x + 2y = 1 for y:

y = -x + 2

Step: Substitute -x + 2 for y in 5x +2y =1 :

5x +2y = 1

5x +2 (-x+2) =1

3x + 4 =1 (simplifiy both sides of the equation)

3x + 4 + - 4 = 1 + -4

(Add -4 to both sides)

3x = -3

3x/3 = -3/3 (Divide both sides by 3)

x = -1


User Kukrt
by
6.3k points